Weather shocks and education in Mongolia - Kati Kraehnert; Valeria Groppo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes the impact of extreme weather shocks on education outcomes in Mongolia. Our focus is on particularly harsh winters that caused mass livestock mortality (called dzud in Mongolian) between 1999 and 2002 and in 2009/2010. The timing of events allows us to analyze both short- and long-term effects of weather shocks on education. Our analysis disentangles the effects by age of exposure. Moreover, we provide new evidence on which households socio-economic characteristics and coping strategies are associated with worse or milder impacts of the shock. The data basis is an unusually detailed household survey that comprises rich information on households shock experience and retrospective information on households pre-shock socio-economic status. Various measures of shock intensity are derived from data on snow depth and livestock mortality. We mainly employ a difference-in-differences econometric approach, which allows to draw causal inference by exploiting exogenous variation in shock exposure across space and age cohorts. Results show that weather shocks negatively affect education both in the short- and in the long-term. Individuals from herding households with poorer socio-economic backgrounds appear to be particularly affected. Individuals exposed during pre-schooling age bear persistent negative human capital effects.
Keywords: I25; Q54; O12; 330